Gate oxide leakage and delay tradeoffs for dual-Tox circuits. - Sultania, A.K.
Gate oxide tunneling current (Igate) is comparable to subthreshold leakage current in CMOS circuits when the equivalent physical oxide thickness (Tox) is below 15 Å. Increasing the value of Tox reduces the leakage at the expense of increased delay, and hence a practical tradeoff between delay and leakage can be achieved by assigning one of two permissible Tox values to each transistor. In this paper, we propose an algorithm for dual-Tox assignment to optimize the total leakage power under delay constraints and generate a leakage/delay tradeoff curve. As compared to the case where all transistors are set to low Tox, our approach achieves an average leakage reduction of 86% under 100 nm models and 81% under 70 nm models. We also propose a transistor and pin reordering technique that has minimal layout impact to further reduce the total leakage current up to 12% and Igate up to 27% without incurring any delay penalty.
Keywords: 100 nm; 70 nm; Delay constraints; Dual oxide thicknesses; Gate oxide leakage; Leakage reduction; Leakage/delay tradeoff curve; Pin reordering; Power delay tradeoffs; Subthreshold leakage; Technology scaling; Total leakage power; Transistor reordering; Dual-TOX circuit